miRNA-1-3p is an early embryonic male sex-determining factor in the Oriental fruit fly Bactrocera dorsalis - Wei Peng (Nature Portfolio, 2020)
In insects, Y chromosome-linked male determining factor can determine sex, but the sex determination factor of the Oriental Fruit fly is unknown. Here the authors show that an autosomal-derived miR-1-3p is enriched in males, suppressing the expression of Bdtra, which is required for female sex determination.